A systematic review of approaches to refeeding in patients with anorexia nervosa. Issue 3 (12th December 2015) - Garber, Andrea K.; Sawyer, Susan M.; Golden, Neville H.; Guarda, Angela S.; Katzman, Debra K.; Kohn, Michael R.; Le Grange, Daniel; Madden, Sloane; Whitelaw, Melissa; Redgrave, Graham W.
ABSTRACT: Objective: Given the importance of weight restoration for recovery in patients with anorexia nervosa (AN), we examined approaches to refeeding in adolescents and adults across treatment settings. Methods: Systematic review of PubMed, PsycINFO, Scopus, and Clinical Trials databases (1960–2015) using terms refeeding, weight restoration, hypophosphatemia, anorexia nervosa, anorexia, and anorexic . Results: Of 948 screened abstracts, 27 met these inclusion criteria: participants had AN; reproducible refeeding approach; weight gain, hypophosphatemia or cognitive/behavioral outcomes. Twenty‐six studies (96%) were observational/prospective or retrospective and performed in hospital. Twelve studies published since 2010 examined approaches starting with higher calories than currently recommended (≥1400 kcal/d). The evidence supports 8 conclusions: 1) In mildly and moderately malnourished patients, lower calorie refeeding is too conservative; 2) Both meal‐based approaches or combined nasogastric+meals can administer higher calories; 3) Higher calorie refeeding has not been associated with increased risk for the refeeding syndrome under close medical monitoring with electrolyte correction; 4) In severely malnourished inpatients, there is insufficient evidence to change the current standard of care; 5) Parenteral nutrition is not recommended; 6) Nutrient compositions within recommended ranges are appropriate; 7) More research is needed in non‐hospital settings; 8) The long‐term impact of different approaches is unknown; Discussion: Findings support higher calorie approaches to refeeding in mildly and moderately malnourished patients under close medical monitoring, however the safety, long‐term outcomes, and feasibility outside of hospital have not been established. Further research is also needed on refeeding approaches in severely malnourished patients, methods of delivery, nutrient compositions and treatment settings.